Toward Somatic Coherence: Five Teachers Engaged In Embodied Ways In Their Professional Development Path - Emond, Geneviève (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2021)
According to Johnson (2007), learning and teaching arise from a human being’s bodily experience in relationship with others and the environment (embodiment). Many teachers perceive and mobilize their bodies in rather unconscious ways. Becoming conscious of their perceptions can help them teach. It can also influence their internal/external coherence (Korthagen, 2004), link between sensations, intentions, and actions. Five elementary teachers participated in a study meant to look at their bodily learning processes, based on a phenomenological methodology (van Manen, 2014) and using somatic approaches (Eddy, 2016). Data analysis shows that they underwent body consciousness learning processes with various effects on their teaching, many posited at a relational level (with students) and all accompanied by a changing perception of self.